Pedunculated polyp of the ileum protruding from a large diverticulum. Issue 2 (21st December 2017) - Iwaya, Yugo; Rowsell, Corwyn; Grantcharov, Teodor; Marcon, Norman E
Abstract : Introduction: A 52-year-old woman presented with iron deficiency anaemia and postprandial right lower quadrant pain. Abdominal examination was unremarkable and laboratory results showed mild anaemia (haemoglobin 11.3 g/dL). Upper and lower endoscopies did not reveal any source of bleeding. Video capsule endoscopy was performed which showed a large polypoid lesion in the mid-ileum (figure 1 ). Abdominal contrast enhanced CT demonstrated a heterogeneously enhancing pedunculated polyp measuring approximately 6 cm (figure 2 ). Retrograde double-balloon enteroscopy was performed which revealed a large pedunculated polyp with hyperplastic-like mucosa protruding from a large diverticulum located approximately 70 cm proximal to the ileocaecal valve (figure 3A ). The stalk appeared to arise from the base of the diverticulum (figure 3B ). A technetium-99m pertechnetate scintigraphy revealed no ectopic gastric mucosa. Question: What is the diagnosis?